Propelling polysulfide redox conversion by d-band modulation for high sulfur loading and low temperature lithium–sulfur batteries. Issue 34 (20th August 2021) - Zeng, Pan; Liu, Cheng; Cheng, Chen; Yuan, Cheng; Dai, Kehua; Mao, Jing; Zheng, Lirong; Zhang, Jing; Chang, Lo-Yueh; Haw, Shu-Chih; Chan, Ting-Shan; Lin, Haiping; et al.
Abstract : Alloying metallic Ni with Fe realizes the upshift of d-band center towards Fermi level, and thus regulates polysulfide adsorbability to accelerate their catalytic conversion. Abstract : The sluggish redox conversion of sulfur species, especially under high sulfur loading, low-temperature, and low electrolyte/sulfur (E/S) ratio conditions, aggravates the shuttle effect that severely deteriorates the electrochemical performance of Li–S batteries. Herein, alloying metallic Ni with Fe increases the Ni–Ni(Fe) bond length and reduces the coordination number of Ni, realizing the upshift of the d-band center towards the Fermi level, and thus regulates sulfur species adsorbability to a rational level to accelerate their catalytic conversion. As a consequence, the Li–S batteries with Ni3 Fe-modified separators exhibit superior rate performances (800 and 645 mA h g −1 at 10 and 15C, respectively) and excellent cycling stability (capacity decay of 0.05% per cycle over 800 cycles at 2.0C). Meanwhile, the stable operation of high areal capacity Li–S batteries under a high sulfur loading of 30 mg cm −2 and a low electrolyte/sulfur ratio of ∼7 µL mg −1 is realized. Besides, benefitting from the enhanced kinetics, the battery can work well at −10 °C, which is rarely achieved by conventional Li–S batteries. Our work provides a promising strategy for designing high-activity electrocatalysts for high-performance and low-temperature Li–S batteries.